Platinum-Catalyzed Deoxygenation of N-Acyloxyamines - Ali, Kashif; Cho, Eun Jin (Synthesis, 2024)
We report a Pt-catalyzed double deoxygenative transformation of N-acyloxyamines, employing PtCl2 catalyst without external ligand under mild conditions. This method facilitates efficient C–N bond formation and can be used to synthesize a broad spectrum of alkylated secondary and tertiary amines with excellent yields. The adaptability and effectiveness of this approach highlight the potential of platinum catalysis to extend beyond traditional synthetic boundaries.
Keywords: platinum; acyloxyamine; deoxygenation; reduction; silane; C–N coupling